Spinal somatosensory evoked potentials in hereditary spastic paraplegia. - Thomas, P K (1981)
Cervical somatosensory evoked potentials elicited by median nerve stimulation were recorded from 18 cases of hereditary spastic paraplegia. Motor and sensory nerve conduction in the median nerve was normal in each. In one third of the patients no spinal evoked potential was detectable. In the remainder the amplitude of the evoked potential was reduced in comparison with a control series; the latency was not significantly different. These changes suggest that a selective degeneration of the centrally directed axons derived from the dorsal root ganglion cells occurs in this disorder. The findings are discussed in relation to previous reports on the pathological appearances.